The South American Fruit Fly: An Important Pest Insect With RNAi-Sensitive Larval Stages - Dias, Naymã; Cagliari, Deise; Kremer, Frederico Schmitt; Rickes, Leticia Neutzling; Nava, Dori Edson; Smagghe, Guy; Zotti, Moisés (Frontiers in Physiology, 2019)
RNA interference (RNAi) technology has been used in the development of approaches for pest control. The presence of some essential genes, the so-called “core genes”, in the RNAi machinery is crucial for its efficiency and robust response in gene silencing. Thus, our study was designed to examine whether the RNAi machinery is functional in the South American (SA) fruit fly Anastrepha fraterculus (Diptera: Tephritidae) and whether the sensitivity to the uptake of dsRNA could generate an RNAi response in this fruit fly species. To prepare a transcriptome database of the SA fruit fly, total RNA was extracted from all the life stages for later cDNA synthesis and Illumina sequencing. After the de novo transcriptome assembly and gene annotation, the transcriptome was screened for RNAi pathway genes, as well as the duplication or loss of genes and novel target genes to dsRNA delivery bioassays. The dsRNA delivery assay by soaking was performed in larvae to evaluate the gene-silencing of V-ATPase, and the upregulation of Dicer-2 and Argonaute-2 after dsRNA delivery was analyzed to verify the activation of siRNAi machinery. We tested the stability of dsRNA using dsGFP with an in vitro incubation of larvae body fluid (hemolymph). We identified 55 genes related to the RNAi machinery with duplication and loss for some genes and selected 143 different target genes related to biological processes involved in post-embryonic growth/development and reproduction of A. fraterculus. Larvae soaked in dsRNA (dsV-ATPase) solution showed a strong knockdown of V-ATPase after 48 h, and the expression of Dicer-2 and Argonaute-2 responded with an increase upon the exposure to dsRNA. Our data demonstrated the existence of a functional RNAi machinery in the SA fruit fly, and we present an easy and robust physiological bioassay with the larval stages that can further be used for screening of target genes at in vivo organisms’ level for RNAi-based control of fruit fly pests. This is the first study that provides evidence of a functional siRNA machinery in the SA fruit fly.